New Paradigm in Millennial Business: A Case Study of Pilona Coffee, Tangerang City - Tri Anggreni; Canggih Gumanky Farunik; Hendra Hendra (Fakultas Bisnis, 2021)
Millennial has its own character of thinking, because when compared to the previous generation who carried out the process of adaptation to the development of information technology, millennial grew and lived with the technology. They thrive with memes, digital markets, electronic money, and social media networks. Virality makes something quickly famous and quickly forgotten, collective memory is limited to how long digital traces can last on the internet. On the basis of that problem, this study was prepared with the question